Teacher Interpersonal Communication Patterns in Improving the Quality of Islamic Religious Education Learning - Ahmad Sholeh (AL-ISHLAH: Jurnal Pendidikan, 2022)
The process of interpersonal communication in learning has not received serious attention from Islamic religious teachers. Teachers are only busy with administrative activities. In contrast to SMA al-Izzah Batu, to improve the quality of learning in this global era, several academic and non-academic programs were opened. Based on this phenomenon, this research was conducted. This study uses a qualitative approach by using the form of a case study (case study). The results of this study are as follows: First, the ethics of interpersonal communication has been applied well by teachers and students at SMA al-Izzah when conducting interpersonal communication. Second, the relationship developed in the PAI learning process at al-Izzah High School related to interpersonal communication is the father-child relationship and the spiritual bathiniyah relationship which in the theory of interpersonal relationship analysis is included in the role model category. Third, the interpersonal communication process carried out by PAI teachers at al-Izzah High School is dialogical and moderate.